PTU-053 Metachronous Extra-Colonic Malignancy in Collagenous Colitis. (17th August 2016) - Dabos, KJ; Yung, DE; Giannakou, A; MacNeill, M; Fineron, P; Plevris, J; Koulaouzidis, A
Abstract : Introduction: Collagenous colitis (CC) is a syndrome of chronic, watery, non-bloody diarrhoea. 1 Its worldwide incidence is increasing; emerging evidence suggests a possible association between CC and malignancy. 2 However, studies thus far have been inconclusive and data on the incidence of metachronous extra-colonic malignancy (MEcM) in CC is scarce. 3 This study aimed to determine the occurrence of MEcM in patients with CC. Methods: Retrospective study; data on MEcM in patients previously diagnosed with CC was collected within NHS Lothian (Scotland) over a 14 year period (Jan 2000 – Nov 2013). Person-years at risk were calculated according to age-specific categories. The standard error ( Se ) was calculated using the Poisson approximation. Relative risk ( RR ) and confidence interval ( CI ) of the age-standardised rate ( ASR ) were compared to publicly available population data for Lothian, Scotland. 4 Results are reported as average ± standard deviation or RR with confidence interval (CI). P values <0.05 were considered statistically significant. Results: In the aforementioned period, 394 patients were diagnosed with CC and included for analysis. Thirty-three (21 F/12 M) developed MEcM, Table 1 . The average age of the group with MEcM was 71.6 ±7.4 years compared to 65.9 ±13.6 years for the remainder of the patients ( P < 0.05). The average duration of follow-up from CC diagnosis to MEcM was 2 ±2.23 years and for the group as a whole was 4 ±3.45 years. The RR for lung cancer (4.63, 1.30;16.49) and total cancers (2.34, 1.38;3.95) in patients with CC was higher compared to population data from Lothian ( P < 0.05 for both). Conclusion: The RR of MEcM, including lung cancer, is higher in patients with CC.The increased RR for lung cancer may be explained by the association between CC and smoking. 5 Further collective data will be useful to clarify other associations. References: 1 Münch A, et al . Microscopic colitis: current status, present and future challenges: statements of the European Microscopic Colitis Group. J Crohn's Colitis 2012;6 :932–945. 2 Freeman HJ. Complications of collagenous colitis. World J gastroenterol 2008;14 :1643. 3 Chan JL, et al . Cancer risk in collagenous colitis. Inflamm Bowel Dis 1999;5 :40–43. 4 http://www.ncin.org.uk/cancer_information_tools/eatlas/guide 5 Vigren L, et al . Is smoking a risk factor for collagenous colitis? Scand J Gastroenterol 2011;46 :1334–1339. Disclosure of Interest: None Declared